Uncovering cynicism in medical training: a qualitative analysis of medical online discussion forums - Peng, Jenny; Clarkin, Chantalle; Doja, Asif (Université d'Ottawa | University of Ottawa, 2018)
The development of cynicism in medicine, defined as a decline in empathy and emotional neutralisation during medical training, is a significant concern for medical educators. We sought to use online medical student discussion groups to provide insight into how cynicism in medicine is perceived, the consequences of cynicism on medical trainee development and potential links between the hidden curriculum and cynicism.
Keywords: qualitative research; world wide web technology